Приближение непрерывных функций операторами Валле Пуссена - Рукасов, В.И. (Український математичний журнал, 2003)
Для верхніх меж відхилень операторів Валле Пуссена від функцій, заданих на дійсній осі, знайдено асимптотичні рівності, які забезпечують розв'язок відомої задачі Колмогорова — Нікольського. For the upper bounds of the deviations of a function defined on the entire real line from the corresponding values of the de la Vallée-Poussin operators, we find asymptotic equalities that give a solution of the well-known Kolmogorov–Nikol'skii problem.